1998
DOI: 10.1021/jp980229p
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Ferric Ion in Water and Conformational Equilibrium

Abstract: 2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
460
1
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 439 publications
(482 citation statements)
references
References 49 publications
19
460
1
2
Order By: Relevance
“…68 It is important to recognize that commonly employed entropy evaluations within the rigid rotor, harmonic oscillator and ideal gas approximations normally overestimate the entropic cost for reactions occurring in solution phase, because ideal gas partition functions do not explicitly take into account hindered translation, rotation and vibration of the solute surrounded by solvent molecules. 25,[69][70][71][72][73][74] For example, Huang and coworkers observed that the calculated standard activation entropy values (-T∆S ‡ calc) consistently overestimate the experimental -T∆S ‡ exp values by ~4-5 kcal/mol at 298K. 71,72 Liang and coworkers also observed that -T∆S ‡ exp values are 50-60% of the computed -T∆S ‡ calc, and in some cases activation entropic costs -T∆S ‡ exp are overestimated by ~11 kcal/mol.…”
Section: Methodsmentioning
confidence: 99%
“…68 It is important to recognize that commonly employed entropy evaluations within the rigid rotor, harmonic oscillator and ideal gas approximations normally overestimate the entropic cost for reactions occurring in solution phase, because ideal gas partition functions do not explicitly take into account hindered translation, rotation and vibration of the solute surrounded by solvent molecules. 25,[69][70][71][72][73][74] For example, Huang and coworkers observed that the calculated standard activation entropy values (-T∆S ‡ calc) consistently overestimate the experimental -T∆S ‡ exp values by ~4-5 kcal/mol at 298K. 71,72 Liang and coworkers also observed that -T∆S ‡ exp values are 50-60% of the computed -T∆S ‡ calc, and in some cases activation entropic costs -T∆S ‡ exp are overestimated by ~11 kcal/mol.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the results of calculations of reaction free energies involving transition-metal ions are highly sensitive to the choice of computational and cluster models. For example, the hydrolysis constants of [Fe(aq)] 3+ calculated from the four independent studies [43][44][45][46] differ by more than 10 pK units. Recent successes in predicting reaction free energies in aqueous solutions have been attributed for the most part to a compensation of errors in the applied cluster/continuum model, density functional, and the basis set.…”
Section: The Hydrated Cumentioning
confidence: 99%
“…Structural and thermodynamic issues are connected, of course, and particularly directly by the quasichemical theory (9)(10)(11)(12)(13)(14)(15)(16)(17). A primitive quasichemical approximation has been developed for the hydration free energy of H ϩ (aq) (4, 7).…”
mentioning
confidence: 99%